Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/ijem-09-2018-0282
|View full text |Cite
|
Sign up to set email alerts
|

E-learning in higher inclusive education: needs, opportunities and limitations

Abstract: Purpose The purpose of this paper is to study the limitations, opportunities and conditions for the development of e-learning in the inclusive education system in the universities. Design/methodology/approach The paper reviews the literature dedicated to e-learning, its application and adaptation in higher inclusive education. Systemic and social approaches were applied to the perception of higher inclusive education for the purposes of this study. The principles of evolutionary economics and institutional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 16 publications
2
34
0
4
Order By: Relevance
“…Teachers feel the need to not only be able to use the technologies, but also to be confident in their use under the judgmental gaze of their digital native students. Competence using ICT would, thus, likely have a positive relationship with the implementation of ICT into the classroom, for both their own development and that of their students (Meskhi, Ponomareva & Ugnich, 2019). Teachers' beliefs about the importance of ICT in the classroom would also likely influence implementation decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers feel the need to not only be able to use the technologies, but also to be confident in their use under the judgmental gaze of their digital native students. Competence using ICT would, thus, likely have a positive relationship with the implementation of ICT into the classroom, for both their own development and that of their students (Meskhi, Ponomareva & Ugnich, 2019). Teachers' beliefs about the importance of ICT in the classroom would also likely influence implementation decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusive education involves acceptance of all students alike irrespective of their diversity and capabilities. Inclusive education implies that the educational system itself should prepare to integrate the students into mainstream rather than just focusing only on the student (Meskhi et al, 2019). They identified that e-learning can be efficient for inclusive education provided it is delivered in conjunction with conventional learning.…”
Section: Hindrances For Inclusive Educationmentioning
confidence: 99%
“…Online learning improves access to education and training, aiming at reducing temporal and spatial problems that can be met in the traditional form of education 4 , 5 . In parallel, online learning has become one of the fastest growing industries, with a market growth rate over 900% since 2000, which is expected to reach in 2025 an impressive total market value of $325 billion 6 . Furthermore, as to the production and provision of online learning courses, the latter, when compared against the conventional Face-to-Face (F2F) ones, have an average consumption of 90% less energy and 85% fewer CO2 emissions produced per student 7 .…”
Section: Introductionmentioning
confidence: 99%